Facile synthesis of nitrogen-doped hierarchical porous lamellar carbon for high-performance supercapacitors. Issue 5 (6th January 2016) - Yang, Wang; Du, Zhiling; Ma, Zhipeng; Wang, Guiling; Bai, Heping; Shao, Guangjie
Abstract : Three-dimensional interconnected N-enriched hierarchical porous lamellar carbon with a multilevel pore structure has been fabricated using waste nitrogen-containing mantis shrimp shell as a carbon precursor and KOH as an impregnation solution. Abstract : Three-dimensional (3D) interconnected N-enriched hierarchical porous lamellar carbon (NPLC) with a multilevel pore structure has been fabricated by a wet impregnation method using waste nitrogen-containing mantis shrimp shell as a carbon precursor and KOH as an impregnation solution. The synthesized NPLC-2 shows a large surface area of 1222.961 m 2 g −1 calculated by the BET method, a hierarchical porous structure analyzed by the density functional theory (DFT) model, and a high nitrogen content of 1.78% quantified by X-ray photoelectron spectroscopy (XPS). Moreover, the NPLC-2 sample exhibits an ultra-high specific capacitance of 312.62 F g −1 at 0.3 A g −1, excellent rate capability with a specific capacitance of 272.56 F g −1 at 20.0 A g −1 and outstanding cycling stability with around 96.26% capacitance retention after 10 000 cycles at a high current density of 20.0 A g −1 . In addition, NPLC-2 presents a high energy density of 15.05 W h kg −1 at 270 W kg −1, and up to 10.12 W h kg −1 even at a large power density of 14 580 W kg −1 . Therefore, the prepared material can be applied in high energy density and high power density demanding fields.